Breathing to harvest energy as a mechanism towards making a liquid metal beating heart. Issue 97 (4th October 2016) - Yi, Liting; Ding, Yujie; Yuan, Bin; Wang, Lei; Tian, Lu; Chen, Chenggang; Liu, Fujun; Lu, Jinrong; Song, Sen; Liu, Jing
Abstract : Simulating nature to manufacture a self-powered device or motor has been an important goal in science and engineering. Abstract : Simulating nature to manufacture a self-powered device or motor has been an important goal in science and engineering. Conventional spontaneous motion has generally been achieved through the Marangoni flow of an organic liquid or water solution. Moreover, as a metallic material mercury has been developed as a beating heart, a kind of self-propulsion example. However, serious safety concerns about mercury restrict its extensive application. This study discovered an important mechanism to realize a GaIn alloy-based liquid metal beating heart by introducing a breathing mechanism in simulating living organisms. With the unique configuration of a semi-submerged liquid metal droplet partially immersed in alkaline solution, such a system produces a surface tension gradient perpendicular to the three-phase contact line which subsequently leads to the oscillation of the droplet and the surrounding solution. This finding suggests a feasible way to fabricate self-oscillating liquid metal motors without input of external electricity or fuels.